Pengaruh Kompetensi Karyawan, Motivasi, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di PT. Berkah Utama Traktor - Raditya Sastrawan; Nur Cahyadi S. (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
Performance is an important aspect for companies. Every company expects employees to work diligently according to their abilities in order to achieve good work results. Without good performance from all employees, the success in achieving goals will be difficult to attain. This research aims to determine the impact of employee competence, motivation, and work environment on employee performance at PT. Berkah Utama Traktor. This research used quantitative. The number of sample for this research consists of 47 permanent employees working at PT. Berkah Utama Traktor. Data collection for this research use of primary and secondary data, using a questionnaire as the data collection technique. This research used multiple linear regression model. The dependent variable in this research is employee performance, while the independent variables are employee competence, motivation, and work environment. The results of this study indicate that employee competence, motivation, and work environment have a positive influence on employee performance.